Os laboratórios de ideias liberais e a batalha ideológica - Faria, Ana Lucia Barbosa (2017)
This study investigates the power and the role of the Liberal Ideas Laboratories in the preservation and building process of the bourgeois hegemony, redefined according to the neoliberal capitalism boundaries, as from the end of the 1970-decade financial economic crisis. Following this goal one analyzed the genesis of the liberal thought in John Locke, as well as the contemporary meaning of this tradition in Friedrich August von Hayek. One tried to decipher the ideological political movement triggered off by the Mont Pélerin Association, whose objective was to start a worldwide struggle of ideas, aiming to legitimate, establish and keep the liberal ideas, making the individuals internalize the conviction that only the spontaneous order of the market is capable of assuring the freedom of the individuals and an everlasting humanity. Since then, a net of interconnected laboratories of liberal ideas has spread to various countries, aiming at spreading the Hayekian thought. The genesis of the crisis which emerged in the end of the 1970’s was also analyzed. A new paradigm for the renegotiation of the Latin American countries external debt was put forward. The recovery of the international financial system implied the downfall of the peripheral economies because the burden of the crisis was massively transferred to them. Finally, this study intended to decipher the connections between the laboratories of ideas, the international financial organisms and the organizational, political and intellectual elites which have enabled the brutal and accelerated ascent of the bourgeois domination toward the bleeding of the working class